Erdogan's Foreign Policy Against Kurds in Syria: A Turkish Military and Political Strategy - Setiawati, Diana; Enno Haya Gladya Naranta (Universitas Muhammadiyah Surakarta, 2022)
The situation in the Middle East is complicated by the need for Turkey to formulate a new military and political strategy . Relations between the Kurds and Turkey since the collapse of the Ottoman caliphate have been strained by the Kurds' desire for autonomous power. Until now, Kurds are still struggling to gain this legitimacy and are transforming into radical and separatist groups. Turkey under Erdogan's leadership underwent political reform from secular to democratic Islam. This includes changing Turkey's strategy to deal with Kurdish militias in Syria because Kurdish militias in Syria are considered dangerous by forming the PKK. The PKK occupies Syria's border with Turkey, so Erdogan devised a special military and political- strategic framework to stem the power of Kurdish militias. Since Turkey was ruled by Recep Tayyip Erdogan, Turkey's foreign policy has used the concept of